Baseline Sensitivity and Toxic Action of the Sterol Demethylation Inhibitor Flusilazole Against Botrytis cinerea - Wang, Yong (Plant disease, 2020)
In the present study, a total of 95 Botrytis cinerea single-spore strains collected from different hosts in Shaanxi Province of China were characterized for their sensitivity to the sterol demethylation inhibitor fungicide flusilazole. The effective concentration for 50% inhibition of mycelial growth (EC50) of flusilazole ranged from 0.021 to 0.372 µg/ml, with an average value of 0.093 µg/ml. Cross-resistance between flusilazole and commonly used fungicides was not detected, and no flusilazole-resistant mutants were induced. Both on detached strawberry leaves and in greenhouse experiments, flusilazole was more effective than the commonly used fungicide carbendazim at reducing gray mold. After culture on PDA plates or detached strawberry leaves, no difference in sclerotia production or pathogenicity was detected between two strains, WG12 (most sensitive to flusilazole) and MX18 (least sensitive to flusilazole). After treatment with flusilazole, however, the two strains lost the ability to produce sclerotia, and oxalic acid and ergosterol contents in mycelium decreased. Interestingly, the inhibition rate of ergosterol content in MX18 was significantly lower than that in WG12. Expression of Cyp51, BcatrD, and Bcmfs1 genes all increased after treatment with flusilazole, especially the Cyp51 and BcatrD genes. However, the expression of Cyp51 gene or BcatrD gene in WG12 and MX18 were significantly different from each other after treatment with flusilazole. In addition, no point mutations in Cyp51 gene were found in MX18. These data suggest flusilazole is a promising fungicide for resistance management of gray mold and also provided novel insights into understanding the resistance mechanism of flusilazole against plant pathogens